Nonconservative behavior of dissolved organic carbon across the Laptev and East Siberian seas - Alling, V; Sanchez-Garcia, L; Porcelli, D; Pugach, S; Vonk, J; van Dongen, B; Morth, C; Anderson, L; Sokolov, A; Andersson, P; Humborg, C; Semiletov, I; et al. (2010)
Climate change is expected to have a strong effect on the Eastern Siberian Arctic Shelf (ESAS) region, which includes 40% of the Arctic shelves and comprises the Laptev and East Siberian seas. The largest organic carbon pool, the dissolved organic carbon (DOC), may change significantly due to changes in both riverine inputs and transformation rates; however, the present DOC inventories and transformation patterns are poorly understood. Using samples from the International Siberian Shelf Study 2008, this study examines for the first time DOC removal in Arctic shelf waters with residence times that range from months to years. Removals of up to 10%-20% were found in the Lena River estuary, consistent with earlier studies in this area, where surface waters were shown to have a residence time of approximately 2 months. In contrast, the DOC concentrations showed a strong nonconservative pattern in areas with freshwater residence times of several years. The average losses of DOC were estimated to be 30%-50% during mixing along the shelf, corresponding to a first-order removal rate constant of 0.3 yr-1. These data provide the first observational evidence for losses of DOC in the Arctic shelf seas, and the calculated DOC deficit reflects DOC losses that are higher than recent model estimates for the region. Overall, a large proportion of riverine DOC is removed from the surface waters across the Arctic shelves. Such significant losses must be included in models of the carbon cycle for the Arctic Ocean, especially since the breakdown of terrestrial DOC to CO2 in Arctic shelf seas may constitute a positive feedback mechanism for Arctic climate warming. These data also provide a baseline for considering the effects of future changes in carbon fluxes, as the vast northern carbon-rich permafrost areas draining into the Arctic are affected by global warming. Copyright 2010 by the American Geophysical Union.